This preview shows page 1. Sign up to view the full content.
Unformatted text preview: n. To find the x-intercepts for an
equation all that we need to do is set y = 0 and solve for x. Likewise to find the y-intercepts for
an equation we simply need to set x = 0 and solve for y.
Let’s take a quick look at an example. Example 2 Determine the x-intercepts and y-intercepts for each of the following equations.
(a) y = x 2 + x - 6 [Solution]
(b) y = x 2 + 2 [Solution]
(c) y = ( x + 1) 2 [Solution] Solution
As verification for each of these we will also sketch the graph of each function. We will leave the
details of the sketching to you to verify. Also, these are all parabolas and as mentioned earlier we
© 2007 Paul Dawkins 156 http://tutorial.math.lamar.edu/terms.aspx College Algebra will be looking at these in detail in the next chapter.
(a) y = x 2 + x - 6
Let’s first find the y-intercept(s). Again, we do this by setting x = 0 and solving for y. This is
usually the easier of the two. So, let’s find the y-intercept(s). y = ( 0 ) + 0 - 6 = -6
2 So, there is a single y-intercept : ( 0, -6 ) .
View Full Document
- Spring '12